Features of Manifestation of Optokinetic Nystagmus in Meniere’S Disease - Makhzuna Tahsinovna Nasretdinova1, Ozod Rakhmatullaevich Nabiev1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The characteristics of optokinetic nystagmus (O?N) were studied in 20 healthy individuals and 30 individualssuffering from Meniere’s disease in remission. The results recorded by the method of electronystagmographyat frequency optokinetic stimulation 66,90 156 and field/min. found that in healthy people, the frequencyof IPOs, the total amplitude and the speed of the slow phase(sp) nystagmus increases proportional to theincrease in the frequency optokinetic stimulation; accordingly, consistently reduced the average amplitudewindow. In Meniere’s disease, O?N indicators are generally characterized by lower values than normal,and an increase in the frequency of optokinetic stimulation is accompanied not only by a more pronounceddecrease in the total amplitude indicators, but also by a decrease in the speed of the slow phase of O?N.After the glycerol load and with positive results of the glycerol test, the quantitative indicators of O?Nincrease in patients, approaching the physiological norm. It is concluded that it is appropriate to study theO?N in Meniere’s disease to clarify the stage of the disease and predict the effectiveness of treatment.